Targeting Cx43 to reduce the severity of pressure ulcer progression - Kwek, Milton Sheng Yi (2024)
In the skin, repeated incidents of ischemia followed by reperfusion can result in the breakdown of the skin and the formation of a pressure ulcer. Here we gently applied paired magnets to the backs of mice to cause ischemia for 1.5 h and then removed them to allow reperfusion. The sterile inflammatory response generated within 4 h causes a stage 1 pressure ulcer with an elevation of the gap junction protein Cx43 in the epidermis. If this process is repeated the insult will result in a more severe stage 2 pressure ulcer with a breakdown of the epidermis 2-3 days later. After a single pinch, the elevation of Cx43 in the epidermis is associated with the inflammatory response with an increased number of neutrophils, HMGB1 (marker of necrosis) and RIP3 (responsible for necroptosis). Delivering Cx43 specific antisense oligonucleotides sub-dermally after a single insult, was able to significantly reduce the elevation of epidermal Cx43 protein expression and reduce the number of neutrophils and prevent the elevation of HMGB1 and RIP3. In a double pinch model, the Cx43 antisense treatment was able to reduce the level of inflammation, necroptosis, and the extent of tissue damage and progression to an open wound. This approach may be useful in reducing the progression of stage 1 pressure ulcers to stage 2.